Enhancing Project Delivery: Implementing an Integrated Project Master Schedule for the LRT Jabodebek PMO - Avianto, Ika (Avenew Indonesia, 2025)
The LRT Jabodebek project, a complex undertaking involving multiple stakeholders and significant national importance, necessitated a robust project management approach. This white paper details how Avenew Indonesia, acting as consultants to the KAI LRT Division PMO, implemented an Integrated Project Master Schedule (IPMS) to overcome challenges related to schedule integration, variance analysis, and PMO capability enhancement. The result was improved project tracking, effective schedule control, and enhanced overall project delivery.